2015
DOI: 10.7860/jcdr/2015/12213.5973
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Colorectal Cancer in Elderly Patients: How Could We Improve Early Outcomes ?

Abstract: Patient characteristics in both groups were compared using Chi-square with Fisher's exact test for qualitative variables. The normality of data was assessed by the the Shapiro-Wilk test and the Kolmogorov-Smirnov test. The Z Kolmogorov-Smirnov statistical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
13
1
Order By: Relevance
“…Emergency surgical treatment of CRC is potential promoter of permanent disability in frail and vulnerable patients, and discharge is often to long-term care facilities. [29,30] In the literature, longer hospitalization is often due to high incidence of Post Operative Delirium (POD). [31] Ansaloni et al affirmed that to minimize POD, associated risk factors of comorbidity, cognitive impairment, psychopathology, and abnormal glycemic control must be identified and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency surgical treatment of CRC is potential promoter of permanent disability in frail and vulnerable patients, and discharge is often to long-term care facilities. [29,30] In the literature, longer hospitalization is often due to high incidence of Post Operative Delirium (POD). [31] Ansaloni et al affirmed that to minimize POD, associated risk factors of comorbidity, cognitive impairment, psychopathology, and abnormal glycemic control must be identified and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors reported that emergency surgery for CRC in patients over 90 years of age can be performed safely [15,26,29,43] . Old age itself is not an independent negative prognostic factor for CRC surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found similar disease specific survival for elderly and young colorectal cancer patients [28][29][30][31] , but difference in overall survival; this means that the increase of mortality in oncogeriatric patients is due to competing causes of death and not to CRC. Consequently decreased survival in the elderly is mainly due to differences in early mortality [28,[32][33][34][35][36] .…”
Section: Surgical Techniques and Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…Advanced age is an important and well-known factor for development of morbidity and mortality in both elective and emergency surgeries [9]. It is also one of the most affecting factor on the surgical outcomes of the patients who undergone urgent operation due to obstructed CRC [10,11]. Since this cancer is an elderly disease, a significant proportion of the patients have comorbid disorders, functional dependency, and limited life expectancy.…”
Section: Discussionmentioning
confidence: 99%